Molecular dynamics investigation of a one‐component model for the stacking motif in complex alloy structures. Issue 2 (11th March 2022) - Yeh, Jung Wen; Tomita, Kouji; Imanari, Yuuta; Uchida, Masaya
Abstract : The stacking motif observed in complex alloys such as the μ‐Al4 Mn phase is investigated by molecular dynamics simulations. Abstract : Developing realistic three‐dimensional growth models for quasicrystals is a fundamental requirement. The present work employs classical molecular dynamics simulations to investigate the adsorption of Al on a close‐packed Al layer containing atomic vacancies. Simulation results show that the adsorbed Al atoms are located preferentially above and below the atomic vacancies in the close‐packed layer, and the results obtained from a one‐component system of atoms interacting via an interatomic pair potential for Al–Al appropriately reproduce the stacking motif seen in complex alloys such as the μ‐Al4 Mn phase. The simulations also reveal the formation of a deformed icosahedron. These results provide new insights into the growth mechanism and origin of complex alloys and quasicrystals.